The Canons 9 and 17 of the Council of Chalcedon (451) in the Light of the Western Synodal Heritage of the 4th Century - Georgy Zakharov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. The article is devoted to the problem of interpretation of the canons 9 and 17 of the Council of Chalcedon (451) which regulate the arbitrage in disputes between clerics. Of particular importance is the prescription to resolve disputes in which the metropolitans participate through an appeal to the exarch of the diocese or the See of Constantinople. These canons are often viewed as the foundations of the ecumenical primacy and special judicial prerogatives of the See of Constantinople in the entire Orthodox Church. Methods. Given the status of Constantinople as the New Rome, the author compares the contents of the rules of the Council of Chalcedon with the decisions of the Council of Serdica (343) and the Council of Rome (378) concerning the judicial prerogatives of the Roman see. Analysis. As a result, the article criticizes the thesis about the similarity of the rules of the Council of Chalcedon with the appeal canons of the council of Serdica, which has become widespread in historiography. At the same time, in the letter of the Council of Rome (378) and in the rescript of the emperor Gratian who responded to this text, we can find some similarity with the Chalcedonian decrees. For example, in the decisions of both councils, there is alternativeness in the choice of the judicial instance. Their common feature is also the idea that it is impossible to conduct a trial of the metropolitan’s case at the provincial level. At the same time, if the decisions of the Council of Rome deal with the accusations in grave crimes, the canons of the Council of Chalcedon speak about arbitration in litigation. Results. Despite some differences, the decrees of the councils in Rome and Chalcedon are inextricably linked with the general tendencies in the development of the system of ecclesiastical organization at the super-provincial level.